PEMIDANAAN PELAKU TINDAK PIDANA PERCOBAAN PEMBUNUHAN DENGAN RENCANA LEBIH DAHULU (PUTUSAN NOMOR. 214/Pid.B/2021/PN Pkb): Criminal of the Criminal of Attempted Murder with Previous Plan (Decision Number 214/Pid.B/2021/PN Pkb) - Chandra Dwijaya Sumule; Vientje Ratna Multiwidjaja (Universitas Trisakti, 2024)
The conviction of the defendant for attempted murder with premeditation is a punishment for the actions of the suspect who was emotional because he was ridiculed by the victim and intended to kill the victim then took a knife into the suspect's boat and stabbed the victim in the neck and then it was not finished because at that time someone flashed a flashlight towards the suspect so the suspect ran away , Based on the study of the decision number 214/Pid.b/PN Pkb. The problems in this study are (1) How is the punishment for the perpetrators of attempted murder with advance planning appropriate based on Article 338 in conjunction with Article 53 of the Criminal Code? and (2) Is the sentence imposed by the judge in accordance with the purpose of sentencing? This research was conducted using a normative legal research type that is descriptive in nature, using primary legal materials, secondary by collecting data from literature studies which are analyzed qualitatively and drawing conclusions using deductive logic. The conclusions of this study are (1) The conviction of the perpetrators of attempted murder with prior planning is not appropriate based on Article 338 jo 53 of the Criminal Code and (2) The conviction by the judge is not in accordance with the purpose of sentencing. The results of this study are related to the facts of the trial and the purpose of the 3R+1D punishment and 13.4 years imprisonment, so the perpetrators should be subject to Article 340 in conjunction with 53 of the Criminal Code.